Tides and their seminal impact on the geology, geography, history, and socio-economics of the Bay of Fundy, eastern Canada - Desplanque, Con; Mossman, David (Atlantic Geology, 2004)
Abstract Tides are an ever-present reality in many coastal regions of the world, and their causes and inﬂuence have long been matters of intrigue. In few places do tides play a greater role in the economics and character of a region and its people than around the shores of the Bay of Fundy in eastern Canada. Indeed, the Bay of Fundy presents a wonderful natural laboratory for the study of tides and their effects. However, to understand these phenomena more fully, some large perspectives are called for on the general physics of the tides and their operation on an oceanic scale. The geologic history of the region too provides key insights into how and why the most dramatic tides in the world have come to be in the Bay of Fundy. Tidal characteristics along the eastern Canadian seaboard result from a combination of diurnal (daily) and semidiurnal (twice daily) tides, the latter mostly dominant. Tidal ranges in the upper Bay of Fundy commonly exceed 15 m, in large part a consequence of tectonic forces that initiated the Bay during the Triassic. The existence and position of the Bay is principally determined by a half-graben, the Fundy Basin, which was established at the onset of the opening of the Atlantic Ocean. Due to the proportions of the Bay of Fundy, differences in tidal range through the Gulf of Maine-Bay of Fundy-Georges Bank system are governed by near resonance with the forcing North Atlantic tides. Although Fundy tide curves are sinusoidal, tide prediction calls for consideration of distinct diurnal inequalities. Overlapping of the cycles of spring and perigean tides every 206 days results in an annual progression of 1.5 months in the periods of especially high tides. Depending on the year, these strong tides can occur at all seasons. The strongest Fundy tides occur when the three elements – anomalistic, synodical, and tropical monthly cycles – peak simultaneously. The closest match occurs at intervals of 18.03 years, a cycle known as the Saros. Tidal movements at Herring Cove, in Fundy National Park, illustrate the annual expected tidal variations. Vigorous quasi-equilibrium conditions characterize interactions between land and sea in macrotidal regions like the Bay of Fundy. Ephemeral on the scale of geologic time, estuaries progressively inﬁll with sediments as relative sea level rises, forcing fringing salt marshes to grow to successively higher levels. Although closely linked to a regime of tides with large amplitude and strong tidal currents, Fundy salt marshes rarely experience overﬂow. Established about 1.2 m lower than the highest astronomical tide, only very large tides are able to cover the marshes with a signiﬁcant depth of water. Peak tides arrive in sets at periods of 7 months, 4.53 years, and 18.03 years. For months on end no tidal ﬂooding of the high marshes occurs. Most salt marshes are raised to the level of the average tide of the 18-year cycle. The exact locations of coastal zone water levels such as mean high water and mean low water is a recurring problem and the subject of much litigation. Marigrams constructed for selected river estuaries illustrate how the estuarine tidal wave is reshaped over its course, to form bores, and varies in its sediment-carrying and erosional capacity as a result of changing water surface gradients. Changing seasons bring about dramatic changes in the character of the estuaries, especially so as ice conditions develop during the second half of the 206-day cycle when the difference in height between Neap tide and Spring tide is increasing, the optimal time for overﬂow in any season. Maximum ice hazard, including build-up of "ice walls" in Fundy estuaries, occurs one or two months before perigean and spring tides combine to form the largest tide of the cycle. Although "ice walls" and associated phenomena pose hazards for man-made constructions, important natural purposes are served which need to be considered in coastal development and management schemes. Tides play a major role in erosion and in complex interactions among Fundy physical, biological, and chemical processes. Recent observations on mud ﬂat grain size alterations, over deepening areas of the sea bed, and changes in the benthic community indicate changing environmental conditions in the Bay, caused possibly by increased hydrodynamic energy in the system.